Active DC-link capacitor harmonic current reduction in two-level back-to-back converter - Shen, Lei; Bozhko, Serhiy; Asher, Greg; Patel, Chintanbai; Wheeler, Patrick (IEEE, 2015)
The paper proposes a method of active switching harmonics current reduction in the DC-link capacitor of a two-level, three-phase, back-to-back converter. Based on the derived analytical solution for switching harmonic currents in the DC-link, it is shown that by specific control over the PWM carriers’ phase angles, the targeted harmonics of the rectifier and the inverter can be synchronized in phase such that their cancellation occurs in the DC-link capacitor. This synchronization is provided by harmonic phase feedback control. The three step procedure to implement the method is detailed in the paper. The effectiveness of the proposed approach is verified experimentally.